Direito inclusivo constitucional: a proteção institucional : a proteção institucional aos grupos vulneráveis - Lima, João Rodolfo Gomes de (2013)
The present work aims to develop a study on Inclusive Constitutional Law (ICL) as a new branch of legal science. The article presents its relevance as to the need of carrying out the principals of our Constitution, as well as ensuring the vulnerable individuals and minority groups the promotion and defense of their rights and the consequent and effective participation in social life. In order to achieve that, we start off from the basic concepts and distinctive models of exclusion, segregation, integration and social inclusion, linking them to the legal content and the regulations of our Higher Law. From then on, we seek the definition of the problem, constitutional basics and object of study of ICL. Finally, we list all the addressed topics, in order to verify whether it is possible to affirm that the Inclusive Constitutional Law can be considered a branch of Legal Science.